Cowpea yield on soils with residues of NPK and natural phosphate fertilizers in succession the area of degraded pasture - Gazel Teixeira, Pedro Emerson; Fernandes, Antônio Rodrigues; Galvão, Jessivaldo Rodrigues; da Silveira Pereira, Wendel Valter; Almeida Casanova, Sandro Rogério; da Costa Alves Filho, Pedro Paulo (Revista Ceres, 2016)
The cultivation of cowpea [Vigna unguiculata (L) Walp] can be an important alternative in succession to maize in areas of degraded pastures due to the use of residue from fertilizers . With this, we aimed to evaluate the productivity of cowpea as a successor culture to undergo corn doses of reactive natural phosphate Arad and combinations with NPK. The experimental design was a randomized block design in a split plot with four replications. The fertilizer was applied in previous cultivation (crop) using four phosphate doses in the form of Arad natural phosphate: 50, 100, 200 and 300 kg ha-1 of P2O5 and the sub-plots in combination with NPK, NK, NK + liming, and control (no liming and fertilizer). The cowpea yield components were evaluated in this work. The residues of P2O5 from the natural phosphate increased the phosphorus content in the plant and influenced the number of grains per pod. The residual effect of NK+ liming and only NK showed better results for the variables grain yield, number of pods per plant, number of seeds per pod and dry mass of aerial part. The residual effect of NPK showed better results for the mass of 100 grains.